New Results on I2-Statistically Limit Points and I2-Statistically Cluster Points of Sequences of Fuzzy Numbers - Ö. Kişi; M. B. Huban; M. Gürdal (Journal of Function Spaces)
In this paper, some existing theories on convergence of fuzzy number sequences are extended to I2-statistical convergence of fuzzy number sequence. Also, we broaden the notions of I-statistical limit points and I-statistical cluster points of a sequence of fuzzy numbers to I2-statistical limit points and I2-statistical cluster points of a double sequence of fuzzy numbers. Also, the researchers focus on important fundamental features of the set of all I2-statistical cluster points and the set of all I2-statistical limit points of a double sequence of fuzzy numbers and examine the relationship between them.